E1231/NMN protects against experimental metabolic syndrome: the central role of SIRT1 in modulating AKT/Nrf2/NFκB signaling - Elmorsy, Elsayed A.; Elashry, Hala A.; Alkhamiss, Abdullah S.; Alsaykhan, Hamad; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; Alsoghair, Mansour; Alharbi, Mariam S.; Gabr, Attia M.; Ellethy, Abousree T.; Khodeir, Mostafa M.; Hassan, Ageeb M.; et al. (Frontiers in Pharmacology, 2025)
Metabolic syndrome (MetS) is a cluster of several disorders where many challenges hinder effective treatment. The downregulation of SIRT1 or inhibition of its activity is implicated in its pathophysiology. We hypothesized that the combined SIRT1 direct activator E1231 and the SIRT1 stabilizer nicotinamide mononucleotide (NMN) could offer a novel approach to mitigate the pathophysiological features of MetS. Our results revealed that E1231 alone or combined with NMN increased SIRT1 level and activity. This SIRT1 activation was accompanied by upregulation in the IRS-1 and activation of AKT. In parallel, the Nrf2 level and activity were increased while the NFκB activity and subsequent inflammatory cytokines were decreased. Additionally, SIRT1 activation was associated with improved insulin resistance, blood pressure, lipid profile, fasting blood glucose, glucose tolerance, and kidney and liver functions. Moreover, improved liver histology, decreased hepatic fibrosis markers, and increased survival rates were observed. These protective functions were counteracted when EX527, a SIRT1 inhibitor, was dually administered with E1231. Furthermore, correlation analysis revealed that SIRT1 was negatively correlated with NFκB, insulin resistance, and oxidative stress, while positive correlations were observed between SIRT1, p-AKT, and Nrf2 activity. Random Forest regression algorithm and partial dependence plots highlighted the significant roles of SIRT1, IRS-1, p-AKT, and NFκB in predicting MetS severity. These analyses underscore the strong interconnections between these signals. This reinforces the central role of SIRT1 in coordinating a multifaceted protective response against MetS. To conclude, SIRT1 alleviates MetS by modulating AKT/Nrf2/NFκB signaling and their interactions. Further research is necessary to validate these findings.